2011
DOI: 10.1016/j.jhealeco.2011.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of a health scare: Education, income and the MMR controversy in the UK

Abstract: One theory for why there is an education gradient in health outcomes is that more educated individuals more quickly absorb new health-related information. The measles, mumps, and rubella (MMR) controversy provides a case where, for a short period, some publicized research suggested that the particular childhood vaccine could have serious side-effects. As the controversy unfolded, uptake of the vaccine by more educated parents decreased relative to that of less educated parents, turning a positive education gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
59
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 61 publications
6
59
1
Order By: Relevance
“…Thus we highlight the importance of newly available information for procedure use. As such, our study relates to other studies that highlight the impact of new information on medical procedure use, as in Price andSimon (2009), Del Bono et al (2011) and Anderberg et al (2011). While these previous studies have focused on patients' responses, our study examines a case in which the released information was subject to an expert debate and was not broadly discussed in the public media.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Thus we highlight the importance of newly available information for procedure use. As such, our study relates to other studies that highlight the impact of new information on medical procedure use, as in Price andSimon (2009), Del Bono et al (2011) and Anderberg et al (2011). While these previous studies have focused on patients' responses, our study examines a case in which the released information was subject to an expert debate and was not broadly discussed in the public media.…”
mentioning
confidence: 72%
“…While our application concentrates on changes on the part of OBs, factors such as the level of maternal education could be an important determinant of changes in CS probability. If-as suggested in models of health production-well-educated individuals are better at processing and acting on information, we would expect highly-educated women to react more strongly to the TBT dissemination (Anderberg et al, 2011;Price and Simon, 2009). Nonetheless, we find no support for the suggestion that mothers with higher bargaining power drive the increase in CS probability (Online Appendix Fig.…”
Section: Robustness Testsmentioning
confidence: 92%
“…14 Of particular interest are articles in which the outcomes were based on attitudes related to the perceived benefits or harms associated with certain interventions, even when these were not evidence-based. For example, the authors of articles on cesarean deliveries without medical indication 15,16 and on refusal to vaccinate children in the United Kingdom 17,18 quoted the inverse equity hypothesis to explain why these behaviors were initially adopted by the better-off within a population.…”
mentioning
confidence: 99%
“…Studies have indicated that more concern has been expressed about the MMR than other forms of immunisation (Macoachie & Lewendon, 2004;Smailbegovic, Laing & Bedford, 2003), emphasising the impact of the controversy. The concern has been such that some parents have refused to vaccinate their children, whilst others have sought out and paid for alternative forms of vaccination, such as separate injections (Anderberg, 2011;Brown et al, 2010).…”
Section: Mothers Responsibility and Immunisationmentioning
confidence: 99%